2022
DOI: 10.1186/s12935-022-02611-0
|View full text |Cite
|
Sign up to set email alerts
|

ANLN and UBE2T are prognostic biomarkers associated with immune regulation in breast cancer: a bioinformatics analysis

Abstract: Objectives To screen and verify differential genes affecting the prognosis of breast cancer. Methods Breast cancer gene expression datasets were downloaded from the GEO database, and original data were analyzed in R. The TIMER database was used to analyze the relationship between ANLN and UBE2T and immune cell infiltration. Results Ten hub-key genes were identified, and survival analysis showed that UB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We construct a risk score containing ANLN, previous studies 19 , 20 have found that the expression of ANLN is closely related to immune infiltration, so we explored whether the risk score containing ANLN can affect immune infiltration of pancreatic cancer. We performed ssGSEA to calculate the immune infiltration score of 24 immune cells in each sample, and the Cox proportional hazard regression method was used to evaluate the relationship between the infiltration of 24 types of immune cells and survival.…”
Section: Resultsmentioning
confidence: 99%
“…We construct a risk score containing ANLN, previous studies 19 , 20 have found that the expression of ANLN is closely related to immune infiltration, so we explored whether the risk score containing ANLN can affect immune infiltration of pancreatic cancer. We performed ssGSEA to calculate the immune infiltration score of 24 immune cells in each sample, and the Cox proportional hazard regression method was used to evaluate the relationship between the infiltration of 24 types of immune cells and survival.…”
Section: Resultsmentioning
confidence: 99%
“…ANLN upregulation has been observed in 21 types of cancers and has been associated with poor OS, DFI, and PFI in most cancers [ 76 ]. Multiple studies have proposed ANLN as a potential molecular marker for predicting breast cancer diagnosis [ 59 , 77 ]. Additionally, ANLN has been recognized as a crucial regulatory factor involved in various signaling events, particularly those related to the cell cycle and nucleocytoplasmic transport pathways [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its importance extends to participation in the PI3K/PTEN signaling pathway, crucial in cellular life-death control [ 66 , 67 ]. Additionally, ANLN ’s interaction with multiple immune cells underscores its indispensable role in the immune system [ 68 , 69 ]. Meanwhile, Interferon regulatory factor 2 (IRF2), a family member of the transcriptional factors, plays an instrumental role in modulating IFN-induced immune responses [ 70 ].…”
Section: Discussionmentioning
confidence: 99%